Transpose of a Matrix


Definition of the Transpose of a Matrix

If M is an m × n matrix, then the transpose of M , denoted by MT, is the n × m matrix obtained by interchanging the rows and columns of matrix M .
These are examples of the transpose of matrices.
a)
Row Matrix
Matrix A has one row and a size (or order) 1 × 3 . The transpose of matrix A is obtained by interchanging the row of the matrix into a column. Hence the transpose of matrix A has a size 3 × 1 and denoted by AT is given by
Transpose Row Matrix

b)
Column Matrix
The transpose of matrix B , which has one column and a size 4 × 1 , is obtained by interchanging the column of the matrix into a row. Hence the transpose of matrix B has an order 1 × 4 and denoted by BT is given by
Transpose of Column Matrix

c)
2 by 3 Matrix
Matrix C has a size 2 × 3 . The transpose of this matrix is obtained by interchanging the rows of the matrix into columns (or columns into rows). Hence the transpose CT of matrix C has an order 3 × 2 and is given by
Transpose of a 2 by 3 Matrix

d)
\( D = \begin{bmatrix} 2 & - 5 & 9 \\ -7 & 0 & 9 \\ 1 & -2 & 11 \end{bmatrix} \)
The transpose of matrix \( D \) with order \( 3 \times 3 \) is obtained by interchanging the rows of the matrix into columns (or columns into rows). Hence the transpose \( D^T \) of matrix \( D \) has an order \( 3 \times 3 \) and is given by
\( D^T = \begin{bmatrix} 2 & -7 & 1 \\ - 5 & 0 & -2 \\ 9 & 9 & 11 \end{bmatrix} \)
Note that the rows the transpose of a given matrix are the columns of the matrix and the columns of the transpose are the rows of the matrix.



Properties of the Transpose of Matrices

Some of the most important properties of the transpose of matrices are given below.

  1.   \( (A^T)^T = A \).
  2.   \( (AB)^T = B^T A^T \)
  3.   \( (A+B)^T = A^T + B^T \)
  4.   \( (k A)^T = k A^T \) , k is a real number.
  5.   \( (A^T)^{-1} = (A^{-1})^T \)
  6.   \( Det(A^T) = Det(A) \).
  7.   \( A^T = A \) if and only if \( A \) is a symmetric matrix.
  8.   \( A^{-1} = A^T \) if and only if \( A \) is an orthogonal (square) matrix.



Examples with Solutions

Example 1
Find the transpose of the matrices:
a) \( A = \begin{bmatrix} 0 & 0 & 1 \\ 1 & 0 & 0 \end{bmatrix} \)      b) \( B = \begin{bmatrix} -2 & 0 & 1 \\ \end{bmatrix} \)      c) \( C = \begin{bmatrix} 5 & -7 \\ 1 & -4 \\ 0 & -1 \\ 7 & -4 \\ \end{bmatrix} \)

Solution
We find the transpose of a matrix by interchanging the rows and columns as follows:
a) \( A^T = \begin{bmatrix} 0 & 1\\ 0 & 0 \\ 1 & 0 \end{bmatrix} \)      b) \( B^T = \begin{bmatrix} -2 \\ 0 \\ 1 \end{bmatrix} \)      c) \( C^T = \begin{bmatrix} 5 & 1 & 0 & 7 \\ -7 & -4 & -1 & -4 \end{bmatrix} \)



Example 2
Matrices \( A \) and \( B \) are given by \( A = \begin{bmatrix} -1 & 0 & 1 \\ 1 & 2 & 0 \end{bmatrix} \) , \( B = \begin{bmatrix} -1 \\ 1 \\ 2 \end{bmatrix} \).
Show that \( (AB)^T = B^T A^T \) (verify property 2 above).

Solution
Calculate \( AB \)
\( AB = \begin{bmatrix} -1 & 0 & 1 \\ 1 & 2 & 0 \end{bmatrix} \begin{bmatrix} -1 \\ 1 \\ 2 \end{bmatrix} = \begin{bmatrix} 3 \\ 1 \end{bmatrix} \)
Determine \( (AB)^T \)
\( (AB)^T = \begin{bmatrix} 3 & 1 \end{bmatrix} \)

Determine \( A^T \) and \( B^T \)
\( A^T = \begin{bmatrix} -1 & 1 \\ 0 & 2 \\ 1 & 0 \end{bmatrix} \) , \( B^T = \begin{bmatrix} -1 & 1 & 2 \end{bmatrix} \)
Calculate \( B^T A^T \)
\( B^T A^T = \begin{bmatrix} -1 & 1 & 2 \end{bmatrix} \begin{bmatrix} -1 & 1 \\ 0 & 2 \\ 1 & 0 \end{bmatrix} = \begin{bmatrix} 3 & 1 \end{bmatrix} \)
Hence \( (AB)^T = B^T A^T \)



Example 3
Let matrix \( A = \begin{bmatrix} -1 & 0\\ 1 & 2 \end{bmatrix} \)
Show that \( (A^T)^{-1} = (A^{-1})^T \) (verify property 5 above).

Solution
Determine \( A^T \)
\( A^T = \begin{bmatrix} -1 & 1\\ 0 & 2 \end{bmatrix} \)
Use the formula of the inverse of a \( 2 \times 2 \) matrix \( \begin{bmatrix} x & y \\ z & w \\ \end{bmatrix}^{-1} = \dfrac{1}{xw - yz} \begin{bmatrix} w & - y \\ - z & x \\ \end{bmatrix} \) to find \( (A^T)^{-1} \)
\( (A^T)^{-1} = -\dfrac{1}{2} \begin{bmatrix} 2 & 0\\ 1 & -1 \end{bmatrix} \)

\( \quad \quad = \begin{bmatrix} -1 & 0\\ -\dfrac{1}{2} & \dfrac{1}{2} \end{bmatrix} \)

Use the same formula of the inverse of a \( 2 \times 2 \) matrix given above to find \( A^{-1} \)
\( A^{-1} = -\dfrac{1}{2} \begin{bmatrix} 2 & 1\\ 0 & -1 \end{bmatrix} \)

\( \quad \quad = \begin{bmatrix} -1 & -\dfrac{1}{2}\\ 0 & \dfrac{1}{2} \end{bmatrix} \)

We now determine \( (A^{-1}) ^T \)
\( (A^{-1}) ^T = \begin{bmatrix} -1 & 0 \\ -\dfrac{1}{2} & \dfrac{1}{2} \end{bmatrix} \)

Hence we conclude that \( (A^T)^{-1} = (A^{-1})^T \).



Example 4
Let matrix \( A = \begin{bmatrix} -1 & 0 & 1\\ 1 & 2 & 2 \\ -2 & 0 & 1 \end{bmatrix} \)
Show that \( Det(A^T) = Det(A) \) (verify property 6 above)

Solution
Calculate \( Det(A) \) using the upper row
Calculate \( Det(A) = -1 ( 2 \times 1 - 0) + 1 (0 - 2(-2) ) = 2 \)

Determine \( A^T \)
\( A^T \begin{bmatrix} -1 & 1 & -2 \\ 0 & 2 & 0 \\ 1 & 2 & 1 \end{bmatrix} \)
Calculate \( Det(A^T) \) using the leftmost column
\( Det(A^T) = -1 ( 2 \times 1 - 0) + 1 ( 0 - 2(-2)) = 2 \)
Hence we conclude that \( Det(A^T) = Det(A) \)



Example 5
Use property 7 above to show that matrix \( A = \begin{bmatrix} 0 & -1 & 3\\ -1 & 2 & 5 \\ 3 & -5 & 1 \end{bmatrix} \) is not a symmetric matrix.

Solution
Determine \( A^T \)
\( A^T = \begin{bmatrix} 0 & -1 & 3 \\ -1 & 2 & -5 \\ 3 & 5 & 1 \end{bmatrix} \)
We can verify that the entry at \( A_{2,3} = 5 \) and the entry at \( A^T_{2,3} = - 5 \), therefore matrices \( A^T \) and \( A \) are not equal which means that matrix \( A \) is not symmetric.



Questions (with solutions given below)

  • Part 1
    Given matrix \( A = \begin{bmatrix} 1 & 1 & -3 \\ -1 & 0 & 0 \end{bmatrix} \), calculate and show that the matrices \( A^T A \) and \( A A^T \) are both symmetric.
  • Part 2
    Given the matrices \( A = \begin{bmatrix} -5 & -2 \\ - 1 & 2 \end{bmatrix} \) and \( B = \begin{bmatrix} 0 & 3 \\ 2 & -3 \end{bmatrix} \) , find the matrix \( (A+B)^T \)
  • Part 3
    Let matrix \( A = \begin{bmatrix} 0 & \dfrac{5}{3 \sqrt 5} & \dfrac{2}{3} \\ \dfrac{1}{\sqrt 5} & - \dfrac{4}{3 \sqrt 5} & \dfrac{2}{3} \\ \dfrac{2}{\sqrt 5} & \dfrac{2}{3 \sqrt 5} & - \dfrac{1}{3} \end{bmatrix} \). Show that \( A A^T = A^T A = \begin{bmatrix} 1 & 0 & 0\\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix} \) and therefore \( A^{-1} = A^T \).



Solutions to the Above Questions



More References and links

{ezoic-ad-1}


Popular Pages



More Info

{ez_footer_ads}